Humor Dan Satire Kartun Media Massa Sebagai Komunikasi Visual Di Era Disrupsi - Diana Suprayuni; Anik Juwariyah (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2019)
The era of disruption provides opportunities in the unique style of delivering persuasive messages through cartoons that illustrate opinions by exaggerating them in mass media cartoons. This study tries to analyze how the mass media represent current phenomena with cartoon media. This research also wants to show that cartoons can be one way to observe people's attitudes towards a phenomenon through humor and satire in it. The method in this research is descriptive qualitative. This research study is grouped into: 1) the target of the study of the development of cartoons and mass media as one of the mass communication media, 2) the target of satire and humor studies in mass communication media specifically viewed from the perspective of cartoons, and 3) the target of the study which is obtained from the public response to cartoons, humor, satire, and mass communication. The results showed that cartoons in the era of disruption could be used as an effective alternative to criticism and mobilizing support for a goal. Cartoons are not only intended as humor, but also powerful tools to drive change. The humor and satire on the card can be said to represent humorous discursive practices that are close to satire which have become discursive land in the mass media. Assuming that humor and satire in cartoons are a form of discourse and even education for the community